Consumer traits key to success of new crop varieties - Nakandi, Jacqueline (Harvest Money, 2024)
This article examines the importance of understanding consumer traits for the successful introduction and adoption of new crop varieties in Uganda. As agriculture evolves, the development of high-yield, resilient crop varieties is essential to improving food security and farmer incomes. However, the success of these innovations is not solely dependent on their agricultural performance; it also requires an understanding of consumer preferences, taste, and market demand. The study highlights how aligning new crop varieties with consumer needs can enhance market acceptance and drive adoption by farmers. It also discusses the role of consumer research in guiding the breeding process and ensuring that new crops meet both market and dietary requirements. By addressing these consumer traits, agricultural innovation can be better positioned for success, contributing to sustainable agricultural development and economic growth in Uganda.